EUGENIO DE OCHOA, TRADUCTOR DE BALZAC: OBSERVACIONES SOBRE UNA VERSIÓN DE JÉSUS-CHRIST EN FLANDRE - Méndez Robles, Pedro Salvador (Anales de Filología Francesa, 2006)
Throughout the XIX century Honoré de Balzac’s novels and short-stories were translated in Spain a lot. “Jésus-Christ in Flandre”, a short-story published in 1831, was translated into Spanish by Eugenio de Ochoa in 1836 and by Ángel Romeral in 1880. Among other aspects,the study of Ochoa’s version raises the question of the so-much discussed issue of the limits of the literary translation. In other words, it makes us wonder to what extend the translator of a literary text can manipulate it and reelaborate the discourse of the original text.